Profil Pemecahan Masalah Siswa Kelas VII dalam Menyelesaikan Soal Cerita Aritmatika Sosial pada Pembelajaran Daring Berdasarkan Kemampuan Matematika di SMP Negeri 4 Palu - Dini Supriati; Muh. Hasbi; Nurhayadi Nurhayadi (Universitas Tadulako, 2021)
The study aims to describe the Problem Solving Class VII In Solving Word Problem Based On Social Arithmetic On Online Learning The Ability Of Mathematics. The research subjects are 3 students, namely students with high, medium and low math abilities. The research uses a qualitative method with a qualitative descriptive approach based on the problem solving steps proposed by Polya. The result showed that the ZR of mathematical abilities, AS of student with moderate mathematical abilities, and MR of student with low mathematics abilities, in solving social arithmetic math problems were as follows: (1) understanding the problem, student ZR, student AS, and student MR understand the given problem by doing repeated reading. ZR student and AS student can identify known information and information asked, but ZR didn’t write down completely while AS couldn’t identify the thing that was asked completely. MR student cannot identify the information that is knows and asked completely, it appears that MR does not understand the problem given, (2) Devising a plan, ZR student make problem solving plan with the formula for buying and selling prices, AS make a problem solving plan using the profit and loss formula. While MR uses the percentage of sales formula, (3) Carrying out the plan, ZR student use their abilities by using the concept of profit or loss, but do not master the arithmetic division operation so they do not complete the final result. AS student carry out problem solving plans well, but to find the purcgase price of AS is not right, and at the stage of calculating te final result, AS does not get the final result because it does not master the division arithmetic operation. While MR at this stage uses an incorrect formula, and cannot complete the final result because MR does not master the devision arithmetic operation, (4) Looking back, ZR, SS and MR students did a rexamination by looking back at the work.